Implementation of Augmented Reality Technology for Human Anatomy Learning Media Using Mobile-Based Gamification Models - Bagus Rosyid Hamdani; Sawali Wahyu; Arief Ichwani; Popong Setiawati (Jurnal Informatika: Jurnal Pengembangan IT, 2026)
SMP Negeri 38 Bekasi is a junior high school that experiences low student learning outcomes in the Science subject, particularly in human body anatomy material. Based on the learning outcome data of eighth-grade students, the low achievement of the Minimum Mastery Criteria (MMC) is largely caused by the abstract nature of anatomy material, which requires strong visualization skills, while the learning process is still dominated by conventional methods based on text and two-dimensional images that are less engaging and interactive for students. To address this problem, the use of technology can be applied through the implementation of Augmented Reality (AR) with a gamification approach in learning media. This study aims to develop a mobile-based learning application on human body anatomy material to improve students’ learning interest and outcomes by presenting three-dimensional models of human body organs, as well as providing interactive quiz features, scoring systems, and leaderboards. The application was developed using a gamification approach and the Multimedia Development Life Cycle (MDLC) method. The results of application testing using the System Usability Scale (SUS) method indicate that the AR Human Body Anatomy application obtained a score of 84.05, which falls into the A or Excellent category, while the Management Dashboard application obtained a score of 80.5, which is also categorized as A. The results show that Science learning using Augmented Reality-based learning media with a gamification approach can facilitate students’ understanding of human body anatomy through three-dimensional visualization technology, increase learning motivation and enthusiasm, and improve student learning outcomes as well as the achievement of the Minimum Mastery Criteria (MMC).